Massive spontaneous hemoperitoneum: known cause from an unknown site - M. B., Anitha; D. P., Santhosh Kumar; Durgesh, N. Siva (International Surgery Journal, 2021)
A 35 years old female presented to casualty with complaints of pain abdomen and vomiting since 3 days. The pain is non radiating type with associated abdominal distension. There is no blood or bike in the vomitus. She has undergone mitral valve replacement 1 month 15 days back and was on prophylactic warfarin medication. On examination vitals were unstable with pallor present and cold extremities. On physical examination. On physical examination: abdominal distension+ guarding+ diffuse tenderness over abdomen+. On USG Abdomen gross collection of blood in the peritoneal cavity. Patient immediately stabilised with 8 units of PRBC. On abdominal laparotomy, active bleeding from right ovarian cyst was observed. Right oophorectomy with peritoneal lavage was done. Hemostasis secured. Postoperative period was uneventful with good post op recovery.